2008
DOI: 10.1097/qad.0b013e3282f423dd
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone mineral density in HIV-infected patients: prevalence and associated factors

Abstract: This cohort-based survey showed a high prevalence of osteopenia and osteoporosis of multifactorial origin. Mechanisms and consequences of these bone disorders need to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
2
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(148 citation statements)
references
References 31 publications
5
128
2
10
Order By: Relevance
“…A second meta-analysis investigated the effect of low bodyweight on BMD and concluded that the low bodyweight may largely account for the high prevalence of low BMD reported in HIV-infected patients [41]. A third study found that older age and low CD4 cell count nadir were independently associated with osteoporosis/osteopenia in women, but the use of ARVs were not related to osteoporosis after adjustment (p = 0.58) [40]. However, in another study of HIV-infected women, PI-containing ARV regimens and longer lopinavir use were associated with lower BMD [42].…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…A second meta-analysis investigated the effect of low bodyweight on BMD and concluded that the low bodyweight may largely account for the high prevalence of low BMD reported in HIV-infected patients [41]. A third study found that older age and low CD4 cell count nadir were independently associated with osteoporosis/osteopenia in women, but the use of ARVs were not related to osteoporosis after adjustment (p = 0.58) [40]. However, in another study of HIV-infected women, PI-containing ARV regimens and longer lopinavir use were associated with lower BMD [42].…”
Section: Generalmentioning
confidence: 99%
“…The few studies looking at the sex association to PI-related GI side effects found that women have higher frequencies of several symptoms compared with men [35][36][37]. Metabolic complications of ARV therapy include insulin resistance and glucose intolerance, dyslipidemia, changes in body fat distribution and, possibly, bone disorders [38][39][40][41][42][43]. Although PI therapies have been linked to glucose and lipid abnormalities [38], the mechanisms underlying other metabolic complications and their relationship to specific ARV therapies is not clearly delineated.…”
Section: Influence Of Sex On Arv-associated Adverse Events In Nonpregmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these same lines, Cazanave and cols. published that the prevalence of osteopenia in HIV-infected patients was 54.6% in men and 51.1% in women, whereas the prevalence of osteoporosis among this population was 33.7% in men and 8.3% in women (22). A systematic review of crosssectional studies by Brown and cols.…”
Section: Hiv and Low Bone Massmentioning
confidence: 99%
“…Therefore, EFV associated vitamin D deficiency may have potential adverse effects on bone health. [21][22][23][24] The growing number of HIV infected pregnant and lactating women on TDF/EFV containing regimens for PMTCT has the potential to have a negative impact on bone health of their infants and young children. Consequently, failure to achieve adequate bone mass during early infancy may predispose these infants to increased risk of childhood fractures and osteoporosis in adulthood.…”
mentioning
confidence: 99%